Exercise-induced asthma - Tan, R. A.; Spector, S. L. (Sports Medicine, 1998)
Exercise-induced asthma (EIA) is characterised by transient airway obstruction occurring after strenuous exertion. A fall of 10% or more in the FEV1 after exercise is diagnostic. Inhalation of large volumes of dry, cold air during exercise leads to loss of heat and water from the bronchial mucosa and airway cooling and drying. Proposed mechanisms for bronchoconstriction include: (i) mucosal drying and increased osmolarity stimulating mast cell degranulation; and (ii) rapid airway rewarming after exercise causing vascular congestion, increased permeability and oedema leading to obstruction. EIA symptoms start after exercise, peak 8 to 15 minutes after exercise and spontaneously resolve in about 60 minutes. A refractory period of up to 3 hours after recovery, during which repeat exercise causes less bronchospasm, has been observed. The amount of ventilation and the temperature of inspired air are important factors in determining the severity of EIA. Greater ventilation and cold, dry air increase the risk for EIA. Education regarding the nature and management of EIA is important not only for asthmatics but also for their families and coaches. With the proper precautions and workout techniques, there is no limit to what individuals with asthma can achieve in sports. Prevention is the main objective in managing EIA. Nonpharmacological measures include warming up before vigorous exertion, covering the mouth and nose in cold weather, exercising in warm, humidified environments if possible and warming down after exercise. Aerobic fitness and good control of baseline bronchial reactivity also help to diminish the effects of EIA. Inhaled beta-agonists are the medications of choice in EIA prophylaxis. Inhaled sodium cromoglycate (cromolyn sodium) or nedocromil may also be used. Agents that may be added if inhaled beta-agonists or sodium cromoglycate are not adequate include anticholinergic agents (such as ipratropium bromide), theophylline, calcium channel blockers, alpha-agonists, antihistamines and oral beta-agonists. Newer agents include antileukotriene agents, inhaled heparin and inhaled furosemide (frusemide).